Performance evaluation of the aerogel RICH counter for the Belle II spectrometer using early beam collision data. (27th August 2020) - Yonenaga, M; Adachi, I; Burmistrov, L; Le Diberder, F; Iijima, T; Iwata, S; Kakimoto, S; Kakuno, H; Karyan, G; Kawai, H; Kawasaki, T; Kindo, H; et al.
Abstract: The Aerogel Ring Imaging Cherenkov (ARICH) counter serves as a particle identification device in the forward end-cap region of the Belle II spectrometer. It is capable of identifying pions and kaons with momenta up to 4\> GeV\> c^-1 by detecting Cherenkov photons emitted in the silica aerogel radiator. After the detector alignment and calibration of the probability density function, we evaluate the performance of the ARICH counter using early beam collision data. Event samples of D^* + → D^0 π^+ (D^0 → K^-π^+) were used to determine the π(K) efficiency and the K(π) misidentification probability. We found that the ARICH counter is capable of separating kaons from pions with an identification efficiency of 93.5 ± 0.6 % at a pion misidentification probability of 10.9 ± 0.9 % . This paper describes the identification method of the counter and the evaluation of the performance during its early operation.